Kajian Pola Tata Ruang pada Bandung Creative Hub dan Bogor Creative Center - Aghisna Arisanti, Sita; Paryoko, Vijar Galax Putra Jagat (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2024)
Spatial pattern arrangement is one of the most important elements in a building. This element can affect a person's interest in visiting the place. Before carrying out a spatial planning pattern, there are steps that must be carried out beforehand, such as conducting an analysis by groupingzoning, space organization, circulation, and also analysis of space requirements. Public buildings likecreative center of course, has many rooms with different functions. Spatial planning in the building must be considered so that the use of space can be utilized as much as possible. This study aims to determine the arrangement of spatial patterns in the Bandung Creative Hub and Bogor Creative Center. This study uses a qualitative descriptive method by comparing the two objects and conducting literature studies through journals, books, or other aligned sources to support the results of the analysis. The results of this study indicate that the two objects have the same spatial planning pattern but with several different facilities and the two objects cover 17 creative economy sub-sectors in Indonesia.